Perceived Importance of Climate Change Adaptation and Mitigation According to Social and Medical Factors Among Residents of Impacted Communities in the United States - Jennifer M. Kreslake (Health Equity, 2019)
Purpose: To determine whether perceived importance of local climate change adaptation and mitigation efforts differs according to social or medical factors among residents of impacted communities. Methods: An online survey was conducted among residents of California (Los Angeles/Orange), Florida (Miami-Dade/Broward), and Arizona (Maricopa) counties in July 2018 (n=605). Multivariable ordered logistic regression measured associations between the perceived importance of adaptation/mitigation approaches and income, race/ethnicity, and health conditions, controlling for age, political party, and county. Results: Lower income was associated with higher perceived importance of improved emergency alerts, government-subsidized costs of household air conditioners and energy-efficient appliances, strengthening buildings against extreme weather, regulation of greenhouse gas emissions, urban planning using ?cooling? technologies, and expanding community gardens/local agriculture. Black respondents perceived evacuation services for those with financial barriers during extreme weather, government-subsidized costs of energy-efficient appliances, and communication from government agencies about local climate impacts and mitigation as significantly more important compared to non-Black, non-Hispanic respondents. Hispanic respondents perceived significantly greater importance of improved emergency alerts and health care access during extreme weather, evacuation services for residents without transportation, government-subsidized costs of energy-efficient appliances, regulation of greenhouse gas emissions, communication from government agencies about local climate impacts and mitigation efforts, and intergovernmental cooperation on mitigation compared to non-Hispanic respondents. Conclusions: Perceptions of the importance of specific local climate actions differ according to race/ethnicity and income. Community engagement is recommended to help local decisions reflect priorities of the most affected residents.